Description of the female of Sattleria sophiae Timossi, 2014 (Lepidoptera: Gelechiidae) - Timossi, Giovanni; Ruzzier, Enrico (Zootaxa, 2020)
The female of Sattleria sophiae Timossi, 2014 is identified on the basis of DNA barcoding, described, illustrated and its habitat is discussed.